2013
DOI: 10.3390/catal3010338
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Alumina and Silica on the Photocatalytic Degradation of Organic Pollutants

Abstract: Practical photocatalysis for degradation of organic pollutants must take into account the influence of other chemicals. Significant Al deposition on titania can occur at naturally occurring concentrations of dissolved Al. This paper reviews the author's work on the influence of deliberately deposited hydrous oxides of aluminium on the behavior of a ~130 m 2 g −1 rutile TiO 2 , and then compares the behavior of deposited alumina with that of deposited silica. On rutile some adsorbed nitrogen is infrared-active.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The most significant decrease for IBU concentration equal to 94% was obtained during the process conducted Additionally, it was determined that the presence of Al 3+ and Fe 3+ ions also decreases the efficiency of photochemical degradation of all investigated pharmaceutical compounds. In research [40] it was confirmed that Al 3+ ions can precipitate on the surface of a photocatalyst and block its photoactivity. Fe 3+ ions can also attract electrons emerging in the process of photoactivation of photocatalyst particles according to Equation (11) it equalled only to 27%.…”
Section: Influence Of Inorganic Cationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The most significant decrease for IBU concentration equal to 94% was obtained during the process conducted Additionally, it was determined that the presence of Al 3+ and Fe 3+ ions also decreases the efficiency of photochemical degradation of all investigated pharmaceutical compounds. In research [40] it was confirmed that Al 3+ ions can precipitate on the surface of a photocatalyst and block its photoactivity. Fe 3+ ions can also attract electrons emerging in the process of photoactivation of photocatalyst particles according to Equation (11) it equalled only to 27%.…”
Section: Influence Of Inorganic Cationsmentioning
confidence: 95%
“…Additionally, it was determined that the presence of Al and Fe ions also decreases the efficiency of photochemical degradation of all investigated pharmaceutical compounds. In research [40] it was confirmed that Al ions can precipitate on the surface of a photocatalyst and block its photoactivity. Fe ions can also attract electrons emerging in the process of photoactivation of photocatalyst particles according to Equation (11) In the case of the solution with AlCl the pharmaceuticals' removal rates obtained after 60 min of UV irradiation during photocatalysis reached correspondingly 91% for DCF, 66% for IBU and only 28% for CBZ.…”
Section: Influence Of Inorganic Cationsmentioning
confidence: 96%
“…Utilization of organic materials for surface modification has typically involved bulk admixtures, which has been exploited successfully in the pigment industry [21,22] or the addition of antioxidants such as vitamin A, E, or C. Even though success has been achieved in both titania-based cosmetic applications and photocatalyst applications, a comparative study and understanding of the balance between these processes is yet to be fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, advanced treatment technologies have gained an interest due to their several advantageous properties. As one of the advanced oxidation technologies, the photocatalytic oxidation process provides an innovative and effective way of non-selective oxidation leading to complete mineralization under the specified conditions [8][9][10][11]. The mechanism of the photocatalytic oxidation process is based on the production of highly-reactive hydroxyl radicals under ultraviolet (UV, λ < 380 nm) irradiation in the presence of a semiconductor photocatalyst (e.g., TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%